CCE: Centro de Ciências Exatas - Peregrino Junior , Roberto; Bisch, Sérgio; Cevolani, Messias; Ferreira, Edileuza; Goronci , Polyanna; Marques , Eliane; Borborema, Arthur; Marcos , Carolina; Santos , Gabrielly; Kach , Hossne; Carvalho , Wesley; Santos , Sâmela; et al. (Revista Guará, 2023)
Resumos de projetos do Centro de Ciências Exatas